The Role Of Health Informatics In Public Health Administration (Journal of Namibian Studies : History Politics Culture, 2022)
Health informatics, encompassing the integration of technology and data in healthcare, has emerged as a pivotal asset in modern public health administration. This article examines the essential role of health informatics in shaping public health policies, enhancing surveillance systems, and fostering population health outcomes. Through the utilization of informatics tools such as electronic health records (EHRs), real-time analytics, and geographic information systems (GIS), public health administrators can bolster disease monitoring, optimize resource allocation, and enact targeted intervention strategies. Despite its transformative potential, challenges such as data security and interoperability persist. Nonetheless, by fostering collaboration, standardizing data exchange, and embracing emerging technologies, health informatics stands poised to revolutionize public health administration worldwide.